A randomized, controlled pilot study of the effects of vitamin D supplementation on balance in Parkinson's disease: Does age matter? - Hiller, Amie L.; Murchison, Charles F; Lobb, Brenna M; O’Connor, Susan; O’Connor, Morgan; Quinn, Joseph F (PLOS ONE, 2018)
Objectives To explore if short term, high dose vitamin D supplementation is safe and improves balance in persons with Parkinson's disease (PD). Methods A pilot randomized, double-blind intervention trial to measure the effects of 16 weeks of high dose vitamin D (10,000 IU/day) on balance as well as other motor and non-motor features of PD. We measured balance, gait, strength, falls, cognition, mood, PD severity, and quality of life before and after 16 weeks of high dose vitamin D supplementation or placebo. All participants also received 1000 mg calcium once daily. Results Fifty-one randomized participants completed sixteen weeks of high dose vitamin D supplementation or placebo. The intervention resulted in a rise in serum concentrations of vitamin D (25-OH) (30.2 ng/ml to 61.1 ng/ml) and was well tolerated with no serious adverse events. Serum vitamin D (25-OH) levels rose steadily and did not suggest a leveling off at the end of the 16 weeks. There was not an improvement in the primary endpoint, balance as measured by the Sensory Organization Test (p = 0.43). A post hoc analysis examining treatment effects in younger (ages 52–66) versus older (ages 67–86) participants found a significant improvement in the SOT of 10.6 points in the younger half of the cohort (p = 0.012). Conclusions Short term, high dose vitamin D supplementation appears safe in persons with PD, but did not significantly improve balance as measured with the Sensory Organization Test in this pilot study population. A post hoc analysis suggests that vitamin D may have potential for improving balance in a younger population with PD. High dose vitamin D supplementation in PD needs further study especially in light of new research suggesting that mega doses and even moderate doses (as low as 4000IU a day) may increase falls in an older populations. Trial registration ClinicalTrials.gov: NCT01119131.